Evaluation of Variable Compressor Technologies - Grigoriadis, Panagiotis; Hoffmann, Alexander; La, Chi Binh (Frontiers in Mechanical Engineering, 2021)
A diverse set of technology solutions are in development for reducing vehicular CO2 emissions. Beside the conventional internal combustion engine, there are hybrid powertrains, fuel cells and full electric vehicles. The challenge is finding the right technology that can be quickly implemented into production as a cost effective solution. From this perspective, the role of turbocharging gets more important for the future. It allows the reduction of a number of engine parts and is an enabler for mature technologies that are known to improve engine efficiency like Miller timing, lean burn, increased EGR dilution and exhaust heat recovery. Improved turbocharging can also benefit other powertrain types like fuel cells. All previously mentioned applications benefit from wider compressor maps and higher compressor ratios. To achieve an extension of the performance map to areas of low mass flow rate, different methods have been discussed with the two most promising being trim reduction introduced by IAV (VTC) and swirl generation. The most common device for inducing a swirl onto the incoming air flow is to use swirl generating wings in front of the compressor wheel. However, putting a single plate in front of the compressor wheel disturbs the recirculating flow which acts positively to extend the compressor map. Trim reduction is well known for its ability to shift the surge line and maintain compressor efficiency. To achieve this, a conical element before the compressor wheel guides the incoming flow to the inner area of the wheel resulting in reduced flow separation. An orifice can also achieve the same effect but with much less axial extension. The advantages and disadvantages of these four measures will be explained using simulation and experimental results to show the potential of each approach. In summary, trim reduction using a conical geometry is still the best performing approach. But taking package restrictions into consideration, an orifice is also a good choice. Whereas swirl producing principles have a moderate impact on shifting the surge line. Finally, a combination will be shown, which extends the compressor performance map for both low and high mass flow rates.